New records of Cosmarium Corda ex Ralfs in lotic environment, adjacent to the Iguaçu National Park, Paraná State, Brazil - Camila Akemy Nabeshima Aquino; Norma Catarina Bueno; Liliane Caroline Servat; Jascieli Carla Bortolini (Hoehnea)
ABSTRACT This study aimed to document the Cosmarium (Desmiadiales, Zygnematophyceae) taxa at a subtropical stream located in an area adjacent to the Iguaçu National Park, an important environmental protection area in the further west of Paraná State. For this purpose, monthly samplings of periphytic material associated to Eleocharis minima Kunth were performed in the period of August 2012 to July 2013. This taxonomic inventory allowed the identification of 37 taxa at specific and infra-specific levels. There were 15 new records for Paraná State: Cosmarium bipunctatum Börgensen, C. clepsydra Nordstedt var. bicardia (Reinsch) Croasdale, C. crenatum var. crenatum Ralfs, C. difficile Lütkemüller var. dilatatum Borge, C. isthmochondrum var. isthmochondrum Nordstedt, C.obsoletum (Hantzsch) Reinsch var. obsoletum, C. ordinatum (Borge) West & West var. ordinatum, C.ornatum Ralfs var. ornatum f. ornatum, C. pseudoconnatum Nordstedt var. pluriradians Scott & Grönblad, C. pseudoretusum F. Ducell. var. pseudoretusum Krieger et Gerlof, C. pyramidatum var. borgei Krieger & Gerloff, C. regnellii var. minimum Eichler & Gutwinski, C. repandum var. minus (West & West) Krieger & Gerloff, C. securiforme Borge var. brasiliense Grönblad and C. variolatum var. variolatum Lundell.